Air inflated Greenhouse As Urban Farming Facilities: Architectural Overview - Syed Zainol Abidin; Ronny D. Nasihien; Hery Budiyanto (NAROTAMA UNIVERSITY, Indonesia)
Urban Farming utilizing land intensification, in order to meet the needs of fresh vegetables and fruits everyday for the community residential / housing in urban areas. Air Inflated Greenhouse as urban farming facilities, can be built and transferred to a residential location / specific housing is easy, safe, fast and lightweight (0,55mm PVC tarpaulin) so that urban farming products closer to consumers in urban settlements, the price impact getting cheaper, but quality. Long-term goal is to develop prototype Air inflated Greenhouse as facilities Urban Farming which fulfills the power, speed, effectiveness, comfort and encourage crops of fruit / vegetable hydroponic hygienic, cheap and profitable, so that the product Air Inflated Greenhouse automatically support an increase in food production, specific target is the availability prototype Air Inflated Greenhouse as Urban Farming facility in order to increase productivity of crops of fruit / vegetable hydroponic hygienic, cheap and profitable, so the high prospects for mass production by SMEs Partners to meet national food requirements. Methods using methods Experiments and Action Research, beginning with the development of design, manufacture, testing and repair of prototype Air Inflated Greenhouse includes (1) a test of strength and endurance of materials Air Inflated Greenhouse to the weather, (2) test material Air Inflated Greenhouse most effective as a component of the structure, (3) test the speed of manufacture, transport, assembly, installation, dismantling Air Inflated Greenhouse, (4) test the temperature, humidity and air pressure in the Air Inflated Greenhouse.